Can the Magmatic Conditions of the Martian Nakhlites be Discerned via Investigation of Clinopyroxene and Olivine Intracrystalline Misorientations? - Griffin, S.; Daly, L.; Piazolo, S.; Forman, Lucy; Cohen, B.E.; Lee, M.R.; Trimby, P.W.; Baumgartner, R.J.; Benedix, Gretchen; Hoefnagels, B. (AMER GEOPHYSICAL UNION, 2022)
Deformation is a near ubiquitous process that is observed within nearly all naturally forming rocks. Electron backscatter diffraction (EBSD) is a technique that enables slip-systems (a form of plastic deformation) to be inferred from intracrystalline misorientations at a comparable scale to the representative CPO analysis (≥300 crystals for the nakhlites). Extensive laboratory and studies on naturally occurring samples have identified preferential mantle condition extrinsic parameters for specific slip-system signatures within olivine and clinopyroxene. Intracrystalline misorientation patterns for olivine and augite (high Ca-clinopyroxene) for 16 different Martian nakhlite meteorites (21 sections) were analyzed and assessed against these known parameters. Investigation of high and low deformation regions within the nakhlites revealed a shift in intracrystalline misorientation patterns for 10 of the 21 sections. Interpreted as both shock (high deformations) and emplacement (low deformation) signatures, the observed variations in deformation patterns for the two main regimes of deformation indicate heterogeneous sampling of the nakhlite source crater. Our findings indicate that shock deformation is prevalent throughout the nakhlites, and that great care needs to be taken when interpreting intracrystalline misorientations of crystals within apparent lower deformation regions.